Volcanic hazards in Mexico-a summary - Stephen A. Nelson (Revista Mexicana de Ciencias Geológicas)
As evidenced by recent eruptions on Earth, volcanic hazards studies can aid scientists and government officials in reducing the danger of volcanic eruptions. Such studies require detailed geologic work in order to assess the areas that might be subject to various types of eruptive behavior from any given volcano. Although nine volcanoes in Mexico have erupted historically and many more have shown relatively recent eruptive activity, a volcanic hazards study is available for only one volcano. A review of the present knowledge of the geologic histories of recently active volcanoes in Mexico reveals that future eruptions are probable, repose times between eruptions of tens of thousands of years are common, and violent eruptions can affect areas at large distances from the volcanoes… In order to continue, download the full text in PDF.